Networked actor theory - (:unkn) unknown (Taideyliopiston Teatterikorkeakoulu, 2021)
The publication grew from the research day arranged in May 2019. And the event originated from the desire to bring together artistic research projects that somehow re-evaluate the agencies of performing bodies and decentre the human figure that has traditionally ruled the stage. I asked you to join me in curating it, and when we were thinking about a name, our colleague Vincent Roumagnac (who is also one of the contributors of the publication) had several fun suggestions, of which Networked Actor Theory stuck. It playfully evokes Actor-Network Theory, developed in the 80s and 90s by Bruno Latour, Michael Callon, Madeleine Akrich, John Law, and others, for which Latour is perhaps best known. But ANT is more method than theory: it’s a way to question how agency is distributed in a mesh of actants, which themselves are co-produced by their relations and can also be divided into other actants. In this way ANT also destabilizes the human as the centre and origin of agency. All the contributing artists in this publication have singular approaches to performing bodies and the politics and technologies that pervade them, and also shake the boundaries of these categories. Each contribution also implicitly gestures towards how dissemination –“writing”–may be conceived in artistic research.
Introduction / Outi Condit & Simo Kellokumpu -- Satyric bodies / Stacey Sacks -- The Gold Bug, Gogol's Nose, and other scenarios / Henna-Riikka Halonen -- Failed mediations – a medium pushing to its limits and breaking apart / Jari Kauppinen -- Where's the remote / Outi Condit -- THE_THEATER_REPRESENTS_A_SEA_AND_ROCKS_ON_ONE_SIDE/AND_ON_THE_OTHER_SOME_TREES_AND_HOUSES_(THE_BACKDROP_AND_ITS_DOUBLE) / Vincent Roumagnac -- Virtual Bodies in Virtual Spaces / Esa Kirkkopelto -- As of yet Unrealized Mind Machine / Otso Huopaniemi.
Keywords: Networked actor theory; Art--Research.; Performing arts; Technology; Virtual reality; Writing; taiteellinen tutkimus; esittävät taiteet; teoriat; ruumiillisuus; toimijuus; teknologia; virtuaalitodellisuus; kirjoittaminen